ENHANCING GLOBAL COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
Fourteen years ago on the historic date of 11th September, one of mankind’s worst tragedies altered the landscape of worldwide global peace, subsequently prompting higher education players to promote ideas on sustainability based on global peace to ensure the continuity of life for mankind. This is a date, which we would prefer to forget, but in fact we need to face it by pooling our knowledge to enhance the spirit of humanity, sense of love and togetherness that transcends borders.